Heat-Killed Streptococcus suis Capsular Type 2 Strains Stimulate Tumor Necrosis Factor Alpha and Interleukin-6 Production by Murine Macrophages - Segura, Mariela (American Society for Microbiology, 1999)
Streptococcus suis capsular type 2 is an important etiological agent of swine meningitis, and it is also a zoonotic agent. Since mononuclear phagocytes have been suggested to play a central role in the pathogenesis of meningitis, the objective of the present study was to evaluate the capacity of whole killed S. suis type 2 organisms to induce the release of the proinflammatory cytokines tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) by murine macrophages. Induction of cytokines was evaluated in the presence or absence of phorbol ester (phorbol 12-myristate 13-acetate [PMA]) costimulation. Results showed that S. suis type 2 stimulated the production of both cytokines in a concentration- and time-dependent fashion. Although large doses of bacteria were required for maximal cytokine release, titers were similar to those obtained with the lipopolysaccharide (LPS) positive control. An increase in cytokine release was observed with both S. suis and LPS with PMA costimulation. Experiments with cytochalasin-treated macrophages showed that the stimulation of cytokine production was phagocytosis independent. When macrophages were stimulated with an unencapsulated mutant, an increase in TNF production was observed, but the absence of the capsule had no effect on IL-6 production. In fact, whereas purified capsular polysaccharide of S. suis failed to induce cytokine release, purified S. suis cell wall induced both TNF and, to a lesser extent, IL-6. IL-6 secretion probably requires some distinct stimuli which differ from those of TNF. Finally, the S. suis putative virulence factors suilysin and extracellular protein EF showed no cytokine-stimulating activity. The ability of S. suis to trigger macrophages to produce proinflammatory cytokines may have an important role in the initiation and development of meningitis caused by this microorganism.